Content Analysis and the Measurement of Meaning: The Visualization of Frames in Collections of Messages - Vlieger, Esther; Leydesdorff, Loet (Public Journal of Semiotics, 2011)
A step-to-step introduction is provided on how to generate a semantic map from a collection of messages (full texts, paragraphs or statements) using freely available software and/or SPSS for the relevant statistics and the visualization. The techniques are discussed in the various theoretical contexts of (i) linguistics (e.g., Latent Semantic Analysis), (ii) sociocybernetics and social systems theory (e.g., the communication of meaning), and (iii) communication studies (e.g., framing and agenda-setting). We distinguish between the communication of information in the network space (social network analysis) and the communication of meaning in the vector space. The vector space can be considered as the space in which the network of relations spans an architecture; words then are not only related, but also positioned. These positions are expected rather than observed and therefore one can communicate meaning.